Patterns and Determinants of Prescribing for Parkinson's Disease: A Systematic Literature Review. (3rd November 2019) - Orayj, Khalid; Lane, Emma
Abstract : Since the discovery of levodopa (L-dopa) in 1967, the range of medications available to treat Parkinson's disease has increased significantly and guidance on the use, efficacy, and safety of these medications has evolved. To assess levels of adherence to national prescribing guidelines and awareness of changes in the efficacy and safety data published in the profiles of medications for the treatment of PD, we have reviewed studies on patterns and determinants of prescribing PD medications conducted in the last 50 years (since the discovery of L-dopa). A systematic literature review was conducted using EMBASE (1967 to March, 2018), Ovid MEDLINE(R) ALL (1967 to March 16, 2018), PsycINFO (1967 to the 2 nd week of March, 2018), and PubMed to identify all studies measuring prescribing patterns of PD medication between 1967 and 2017. Study design, source of data, country, year of study, number of patients and/or prescriptions, unit of analysis, prescribing determinants, and percentage utilisation of PD medications were extracted where possible. 44 studies examining prescribing patterns and/or prescribing determinants across 17 countries were identified. Unsurprisingly, L-dopa was the most commonly prescribed medication in all studies, accounting for 46.50% to 100% of all prescriptions for PD. In several studies, the prescribing rate of ergot-derived dopamine agonists (DAs) decreased over time in concordance with guidance. In contrast, the prescribing rates of non-ergot DAs increased over the last ten years in most of the included studies. In examining prescribing factors, two major categories were exemplified, patients' factors and prescribers' factors, with patients' age being the most common factor that affected the prescription in most studies. In conclusion, L-dopa is now the most commonly prescribed medication for cases of PD but there is large variation in the prescribing rates of catechol-O-methyltransferase (COMT) inhibitors, monoamine oxidase B (MAO-B) inhibitors, amantadine, and anticholinergics between countries. New studies examining the effects of recent clinical trials and measuring the prescribing rates of newly approved medications are warranted.